2023
DOI: 10.1007/s00401-023-02608-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent atypical teratoid/rhabdoid tumors (AT/RT) reveal discrete features of progression on histology, epigenetics, copy number profiling, and transcriptomics

Abstract: Atypical teratoid/rhabdoid tumors (AT/RT) are the most common malignant brain tumors manifesting in infancy. They split into four molecular types. The major three (AT/RT-SHH, AT/RT-TYR, and AT/RT-MYC) all carry mutations in SMARCB1, the fourth quantitatively smaller type is characterized by SMARCA4 mutations (AT/RT-SMARCA4). Molecular characteristics of disease recurrence or metastatic spread, which go along with a particularly dismal outcome, are currently unclear. Here, we investigated tumor tissue from 26 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This high percentage may be surprising, however, similar studies on other types of tumor reported remarkable genomic stability with regard to somatic mutations, genome-wide methylation patterns and chromosomal copy number abnormalities. [34][35][36][37] These studies were also similar to our present work finding no elevated genetic discordance in patients that had received adjuvant radio/ chemotherapy between the primary tumor and recurrence. Therefore, these 12 recurrent ITAC were indeed recurrences and not second primary tumors.…”
Section: Discussionsupporting
confidence: 88%
“…This high percentage may be surprising, however, similar studies on other types of tumor reported remarkable genomic stability with regard to somatic mutations, genome-wide methylation patterns and chromosomal copy number abnormalities. [34][35][36][37] These studies were also similar to our present work finding no elevated genetic discordance in patients that had received adjuvant radio/ chemotherapy between the primary tumor and recurrence. Therefore, these 12 recurrent ITAC were indeed recurrences and not second primary tumors.…”
Section: Discussionsupporting
confidence: 88%
“…5k), suggesting that high cell density areas in PF-EPN-A are generally more transcriptionally active and might play a more active role in tumor propagation. dense (c, d, h, i) and cell-dense (e, f, j, k d, e, i, and j Primary tumors and their relapses differ in respect to cell density, DNA methylation and frequency of chromosome 1q gains and 6q losses CNS tumor relapses tend to acquire more aggressive biology upon relapse in many cases, one example being atypical teratoid/rhabdoid tumors, as recently described by Johann, Altendorf et al [17]. To understand possible prognostic implications of cell density in primary PF-EPN-A, we quantified the proportion of cell-dense areas in nine primary ependymomas and their corresponding relapses, which revealed a mean increase of cell-density in progressive disease (> fourfold increase of the proportion of celldense areas in the respective primary).…”
Section: High and Low Cell Density Areas In Pf-epn-a Have A Distinct ...mentioning
confidence: 83%
“…CNS tumor relapses tend to acquire more aggressive biology upon relapse in many cases, one example being atypical teratoid/rhabdoid tumors, as recently described by Johann, Altendorf et al [ 17 ]. To understand possible prognostic implications of cell density in primary PF-EPN-A, we quantified the proportion of cell-dense areas in nine primary ependymomas and their corresponding relapses, which revealed a mean increase of cell-density in progressive disease (> fourfold increase of the proportion of cell-dense areas in the respective primary).…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosine kinase receptor genes were overexpressed in relapse in ATRT-TYR tumors, while ATRT-SHH relapse displayed higher expression of genes associated with metastases. 146 …”
Section: Future Directions – Discussion and Outlookmentioning
confidence: 99%
“…Tyrosine kinase receptor genes were overexpressed in relapse in ATRT-TYR tumors, while ATRT-SHH relapse displayed higher expression of genes associated with metastases. 146 Paassen et al developed a series of ATRT tumoroids and performed extensive drug screening. In contrast to suggestions by Altendorf et al, tyrosine kinase inhibitors were significantly more effective in ATRT-MYC tumoroids when compared to ATRT-SHH.…”
Section: Treatment Adjustments -The Role Of Molecular Subgroupsmentioning
confidence: 99%